2006
DOI: 10.1007/s00003-006-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Six-year monitoring of non-target arthropods in Bt maize (Cry 1Ab) in the European corn borer (Ostrinia nubilalis) infestation area Oderbruch (Germany)

Abstract: This study was performed in the Oderbruch region, a landscape where Ostrinia nubilalis occurs in high densities. From 2000 to 2005, field pairs (half-fields) planted with Bt maize (Cry 1Ab) and a conventional maize variety, respectively, were investigated using different monitoring methods (visual counts, wholeplant harvesting and pitfall trapping) to determine densities of taxa on plants, activity densities and diversity of ground-dwelling arthropods. A total of 48 taxa were determined in counts and 90 in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Our data showed no signiÞcant difference in their abundances in Bt soybean plots compared with those in the recipient cultivar. Our results were consistent with previous data showing that the population densities of aphids and thrips did not differ between Bt and non-Bt maize Þelds by 6-yr survey in Germany (Schorling and Freier 2006). Likewise, no signiÞcant difference was detected between Bt and non-Bt rice Þelds in population densities of six sucking pest species including planthoppers, Sogatella furcifera (Horváth), Nilaparvata lugens (Stål), and Laodelphax striatellus (Fallé n), and three species of leafhoppers, Nephotettix cincticeps (Uhler), Thaia subrufa (Motschulsky), and Recilia dorsalis (Motschulsky) (Chen at al.…”
Section: Discussionsupporting
confidence: 95%
“…Our data showed no signiÞcant difference in their abundances in Bt soybean plots compared with those in the recipient cultivar. Our results were consistent with previous data showing that the population densities of aphids and thrips did not differ between Bt and non-Bt maize Þelds by 6-yr survey in Germany (Schorling and Freier 2006). Likewise, no signiÞcant difference was detected between Bt and non-Bt rice Þelds in population densities of six sucking pest species including planthoppers, Sogatella furcifera (Horváth), Nilaparvata lugens (Stål), and Laodelphax striatellus (Fallé n), and three species of leafhoppers, Nephotettix cincticeps (Uhler), Thaia subrufa (Motschulsky), and Recilia dorsalis (Motschulsky) (Chen at al.…”
Section: Discussionsupporting
confidence: 95%
“…In a previous study on long-term monitoring of Bt corn, Schorling and Freier (2006) reported that Bt corn did not have a signiÞcant impact on arthropod community. Similarly, Priestly and Brownbridge (2009) concluded from their 2-yr study that environmental conditions and crop-management practices had the most signiÞcant impact on arthropod community rather than crop type.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Bt maize has not encountered the serious problems with secondary insect pests stemming from experiences with Bt cotton (Hellmich et al 2008). For example, in Germany, no difference in the population densities of aphids, thrips, and heteropterans were found after 6 yr of monitoring nontarget arthropods in Bt maize Þelds (Schorling and Freier 2006). With regard to Bt rice, the problems encountered with Bt cotton are not expected to occur.…”
Section: Discussionmentioning
confidence: 94%